Electrolytic galvanic pile with high oxygen evolution performance, anode oxygen evolution electrode contained in electrolytic galvanic pile and application of anode oxygen evolution electrode

The IrO2 particles generated by heat treatment are coated on the surface of the porous support, and a high-performance porous IrO2 electrode is prepared, which solves the problem of slow kinetics of the anode oxygen evolution reaction in AEMCO2ER technology, achieves high activity and long life of the electrode, and reduces costs.

CN119615234APending Publication Date: 2025-03-14SHENZHEN INST OF ADVANCED TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411793653.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the existing AEMCO2ER technology, the kinetics of the anode oxygen evolution reaction are slow, resulting in high anode potential, increasing the risk of AEM film being broken down, shortening the service life, and difficult to meet the requirements of industrial economics.

Method used

The IrO2 particles generated by heat treatment are uniformly coated and loaded on the surface of the porous support to prepare high-performance, long-term stable porous IrO2 electrodes, which replace the electrodes prepared by traditional polymer binders.

Benefits of technology

The oxygen evolution activity and service life of the electrode are improved, the catalyst load and preparation cost are reduced, the bonding force between the electrode and the porous substrate is enhanced, and the cycle stability is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615234A_ABST
    Figure CN119615234A_ABST
Patent Text Reader

Abstract

Compared with a porous IrO2 electrode prepared by a traditional polymer binder, the oxygen evolution electrode prepared by the method provided by the invention has the following two advantages: (1) the polymer binder is canceled, and the hydrophilicity and activity of the surface of the electrode are improved; and (2) the binding force between the catalyst and the porous substrate is remarkably enhanced by IrO2 particles generated by heat treatment, so that the service life of the electrode is prolonged, and the cycling stability of the electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy and environmental protection technology, and in particular to an electrolytic cell stack with high oxygen evolution performance, an anode oxygen evolution electrode contained therein, and applications thereof. Background Art

[0002] With the increasing awareness of environmental protection and the rapid development of renewable energy generation technology, it is imperative to develop new renewable energy technologies to absorb excess green electricity. Among new energy technologies, lithium battery energy storage, water electrolysis hydrogen production and carbon dioxide electroreduction (CO2ER) technology can be coupled with renewable energy (such as wind power and photovoltaic) power generation technology to achieve the transmission and storage of renewable energy across time and space dimensions, which can effectively reduce CO2 emissions. Among them, anion membrane carbon dioxide electroreduction (AEMCO2ER) technology has been considered as one of the efficient carbon reduction technologies. Up to now, although AEMCO2ER technology has made some progress, the challenges of industrialization in the short term are still huge. Among them, the slow kinetics of oxygen evolution reaction seriously hinders the splitting of H2O molecules at the anode, resulting in high anode potential, greatly increasing the risk of AEM membrane breakdown, thereby seriously shortening the service life of AEM, making it difficult to meet the requirements of industrial economy. Therefore, improving the efficiency of oxygen evolution reaction and extending the service life of AEM have become the key bottlenecks in the current technological development.

[0003] Iridium dioxide (IrO2) is considered to be a key material to solve this problem due to its excellent oxygen evolution catalytic performance. IrO2 has the characteristics of high activity and low overpotential, which can effectively improve the efficiency of oxygen evolution reaction and thus reduce the anode potential. However, the traditional CCM (catalyst-coated membrane) process has significant shortcomings in practical applications: on the one hand, the IrO2 loading is relatively high (1-2 mg / cm 2 ), resulting in high costs; on the other hand, the economic efficiency of the equipment over its entire life cycle is poor due to the difficulty in recycling the catalyst. Therefore, relying solely on the high efficiency of IrO2 itself is not enough to meet industrial requirements, and further optimization is needed in material design and preparation process. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes an innovative method for preparing porous IrO2 electrodes. IrO2 is generated by heat treatment, and nano-IrO2 particles are uniformly coated and loaded on the surface of a porous support to prepare a high-performance, long-term stable porous IrO2 electrode. Compared with porous IrO2 electrodes prepared with traditional polymer binders, this method has the following two major advantages: (1) The polymer binder is eliminated, thereby improving the hydrophilicity and activity of the electrode surface; (2) The IrO2 particles generated by heat treatment significantly enhance the bonding force between the catalyst and the porous substrate, thereby improving the service life and cycle stability of the electrode. This design provides important support for reducing the cost of AEMCO2ER technology and promoting its industrial application.

[0005] In order to solve the above technical problems, the present invention proposes an electrolytic stack with high oxygen evolution performance, wherein the anode is an IrO2 oxygen evolution electrode, and the specific preparation method includes:

[0006] In the first step, the porous support is acid-etched to remove the surface oxide layer;

[0007] The second step is to heat treat part of the iridium source to form a small amount of IrO2 anti-passivation layer on the surface of the porous support;

[0008] The third step is to prepare a mixture of iridium source, nano-IrO2 and polymer binder;

[0009] The fourth step is to spray the mixture prepared in the third step uniformly on the surface of the porous support body treated with anti-passivation in the second step;

[0010] The fifth step is to decompose the polymer binder in the sprayed mixture through heat treatment, and make the IrO2 formed by the iridium source coat the nano-IrO2 and load it on the surface of the porous support body that is resistant to passivation treatment, so as to obtain a highly active and highly stable porous IrO2 electrode.

[0011] Wherein, the iridium source includes at least one of chloroiridic acid, potassium hexachloroiridate, ammonium chloroiridate, ammonium chloroiridate, iridium trichloride, and iridium acetate.

[0012] Wherein, the porous support body includes at least one of titanium felt, matrix porous titanium (MPT), foam titanium, foam iron, foam nickel iron, carbon paper, and carbon cloth.

[0013] Wherein, the polymer binder includes at least one of Nafion, polyvinyl alcohol, carboxymethyl cellulose, epoxy resin and polyacrylamide.

[0014] Among them, in the second step, the loading range of IrO2 anti-passivation layer is 0.05-0.2mg / cm 2 .

[0015] Wherein, in the third step, the mass ratio of the iridium source, nano-IrO2 and polymer adhesive is controlled at 1:2:4.

[0016] The electrolytic cell stack can be applied to waste gas carbon dioxide treatment and water electrolysis to produce hydrogen.

[0017] The present invention also provides an anode IrO2 oxygen evolution electrode prepared by the method.

[0018] The iridium loading of the anode oxygen evolution electrode is 0.1-0.3 mg / cm 2 .

[0019] Among them, the anode oxygen evolution electrode is used in the anode oxygen evolution reaction of carbon dioxide reduction, proton exchange membrane water electrolysis to produce hydrogen, and nitrogen reduction.

[0020] Beneficial Effects of the Invention

[0021] 1) The iridium oxide loading of the IrO2 electrode prepared by the present invention is low, which is 0.1-0.3 mg / cm 2 , much lower than the 1.0-3.0 mg / cm of commercial electrodes 2 .

[0022] 2) The IrO2 electrode prepared by the present invention has high oxygen evolution activity, and in 0.01M sodium sulfate solution, 50mAcm -2 The potential of the current density is only 1.86V, which is lower than the 1.89V of the commercial electrode; the cell voltage of carbon dioxide reduction (CO2 to CO) in pure water at room temperature is 2.95V, which is 3.4V lower than the cell voltage of the electrolytic cell equipped with commercial electrodes.

[0023] 3) The IrO2 electrode prepared by this high-temperature heat treatment technology has a strong bonding between the catalyst and the porous support compared to the IrO2 electrode prepared by the traditional polymer binder. After a 100-hour carbon dioxide reduction (CO2 to CO) test, the IrO2 shedding rate was 4.6%, which is lower than the commercial 50.4%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The loading of 0.05 mg Ir / cm prepared in Example 1 2 Physical picture of anti-passivation layer MPT;

[0025] Figure 2 The loading of 0.1 mg Ir / cm prepared in Example 2 2 Physical picture of anti-passivation layer MPT;

[0026] Figure 3 The load of 0.2 mg Ir / cm prepared in Example 3 2 Physical picture of anti-passivation layer MPT;

[0027] Figure 4 The linear voltammetric curve of the IrO2 porous electrode prepared in Example 1-3 in 0.01M sodium sulfate solution;

[0028] Figure 5 The actual picture of the anode electrode after the test of Example 4-5 and its catalyst mass loss rate;

[0029] Figure 6 The relationship between the electrolytic cell voltage and time in Example 4-5 is shown. DETAILED DESCRIPTION

[0030] In order to enhance the activity and long-term stability of the IrO2 electrode, the IrO2 generated by the heat-treated iridium source used in the present invention can not only serve as a highly active oxygen evolution catalyst and an anti-passivation layer of a porous support, but also enhance the binding force between nanocatalysts and nanocatalysts, and between nanocatalysts and the support, thereby ensuring the long-term stability of the electrode and increasing the service life of the electrode.

[0031] At present, the mainstream porous IrO2 electrodes are mostly prepared by magnetron sputtering, hydrothermal method and high-temperature heat treatment technology. Although the nano-IrO2 catalyst porous electrodes prepared by magnetron sputtering and hydrothermal method have high catalytic activity, the magnetron sputtering process is complicated and costly; the catalyst prepared by hydrothermal method has poor bonding with the substrate and is easy to fall off, so it cannot be prepared and applied industrially. Although the porous IrO2 electrode prepared by heat treatment method has good bonding between the catalyst and the substrate, it has no nano-morphology and poor electrochemical activity.

[0032] Therefore, the present invention uses IrO2 generated from an iridium source as a binder through a heat treatment technology, and coats and loads nano IrO2 on the surface of a porous support to form a highly active and long-term stable porous IrO2 electrode. This electrode not only has good oxygen evolution activity, but also has a strong combination of the catalyst and the matrix, and a low catalyst shedding rate. In addition, this electrode not only has a simple preparation process, a low iridium loading, but also can significantly reduce the electrode preparation cost. This preparation method enables the prepared porous IrO2 electrode to not only obtain the strong binding force between the catalyst and the support given by the traditional heat treatment technology, but also has the high activity and low loading of the nano catalyst.

[0033] The present invention firstly removes the oxide layer and impurities on the surface of the porous support body through oxalic acid etching; then forms an IrO2 anti-passivation layer on the surface of the porous support body through high-temperature heat treatment of a part of the iridium source; then uniformly sprays the iridium source, nano-IrO2 and a polymer binder on the anti-passivation treated surface of the porous support body; finally, calcines in an air atmosphere, and the generated IrO2 coats the nano-IrO2 and is loaded on the surface of the porous support body to obtain a highly active and long-term stable porous IrO2 electrode.

[0034] Specifically, the present invention provides a method for preparing an anode IrO2 oxygen evolution electrode, comprising:

[0035] In the first step, the porous support is acid-etched to remove the surface oxide layer;

[0036] The second step is to heat treat part of the iridium source to form a small amount of IrO2 anti-passivation layer on the surface of the porous support. The loading range of IrO2 anti-passivation layer is 0.05-0.2 mg / cm 2 ;

[0037] The third step is to prepare a mixture of iridium source, nano-IrO2 and polymer binder;

[0038] The fourth step is to spray the mixture prepared in the third step uniformly on the surface of the porous support body treated with anti-passivation in the second step;

[0039] The fifth step is to decompose the polymer binder in the sprayed mixture through heat treatment, and make the IrO2 formed by the iridium source coat the nano-IrO2 and load it on the surface of the porous support body that is resistant to passivation treatment, so as to obtain a highly active and highly stable porous IrO2 electrode.

[0040] Furthermore, the iridium source includes at least one of chloroiridic acid, potassium hexachloroiridate, ammonium chloroiridate, ammonium chloroiridate, iridium trichloride, and iridium acetate.

[0041] Furthermore, the porous support body includes at least one of titanium felt, matrix porous titanium (MPT), foam titanium, foam iron, foam nickel iron, carbon paper, and carbon cloth.

[0042] Furthermore, the polymer binder includes at least one of Nafion, polyvinyl alcohol, carboxymethyl cellulose, epoxy resin, and polyacrylamide.

[0043] Furthermore, a porous support of a suitable area was immersed in a 0.5 M oxalic acid solution, treated at 80° C. for 10 minutes, and dried naturally for later use.

[0044] Furthermore, in the second step, the iridium source ethanol solution is evenly coated on the surface of the acid-washed porous support, dried naturally, and then transferred to a muffle furnace with a heating rate of 10°C / min, kept at 450°C for 30 minutes, and cooled to room temperature.

[0045] Furthermore, in the third step, the iridium source, nano-IrO2 and polymer adhesive are uniformly dispersed and mixed in a certain mass ratio, and the mass ratio of the iridium source, nano-IrO2 and polymer adhesive is controlled at 1:2:4.

[0046] Furthermore, in the fourth step, a uniform mixture of the iridium source, nano-IrO2 and polymer binder is sprayed on the surface of the porous support body carrying the anti-passivation layer and dried at 60°C.

[0047] Furthermore, in the fifth step, the heating rate of the muffle furnace is 10°C / min, the heat treatment temperature is 450°C, the heat treatment time is 30 minutes, and finally the temperature is naturally reduced to room temperature.

[0048] The present invention also provides an anode IrO2 oxygen evolution electrode, which is prepared by the method as described above.

[0049] The iridium loading of the anode oxygen evolution electrode is 0.1-0.3 mg / cm 2 .

[0050] The anode oxygen evolution electrode can be used in the anode oxygen evolution reactions of carbon dioxide reduction, proton exchange membrane water electrolysis to produce hydrogen, and nitrogen reduction.

[0051] The present invention also provides a novel electrolytic stack with high oxygen evolution performance, which is composed of an anode side and a cathode side component, and is separated by an anion exchange membrane as the core. The anode side includes an anode end plate, an anode insulating plate, an anode current collector plate, an anode flow field plate, and the anode IrO2 oxygen evolution electrode described above. The cathode side component corresponds to the anode side structure, including a cathode end plate, a cathode insulating plate, a cathode current collector plate, a cathode flow field plate, and a cathode gas diffusion electrode. The cathode gas diffusion electrode is composed of a gas diffusion layer and a catalyst layer made of carbon material (such as carbon paper or carbon cloth) to ensure conductivity and air permeability.

[0052] The anode and cathode gas diffusion electrodes are located on both sides of the anion exchange membrane, and the catalyst layer is close to the anion exchange membrane, together forming a membrane electrode assembly. To enhance the structural stability of the stack, a PPS frame layer can be added to the outside of the anode gas diffusion layer and the cathode gas diffusion layer. In addition, all components are arranged from the outside to the inside, with the anode assembly close to the anode diffusion electrode and the cathode assembly close to the cathode diffusion electrode, to optimize the reaction gas distribution and electron transmission path, thereby achieving efficient electrolysis performance.

[0053] The following embodiments and drawings are used to describe the implementation methods of the present invention in detail, so that the implementation process of how the present invention applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0054] Oxygen evolution performance evaluation

[0055] Cut 1×2cm 2 Specifications The electrodes prepared in Examples 1 to 3 below were clamped on a Pt sheet electrode; the counter electrode was a Pt sheet electrode (1×1 cm 2); the reference electrode was a saturated Ag / AgCl electrode; the electrolyte was 0.01M sodium sulfate, the linear voltammetric curve scanning range was 1.0-3.5V, and the scanning rate was 5mV / s;

[0056] Reversible hydrogen electrode potential conversion, according to the formula

[0057] E(RHE)=E(Ag / AgCl)+0.0592*pH-iR*90%, i is current and R is impedance.

[0058] Example 1

[0059] The iridium loading was 0.05 mg / cm 2 Porous IrO2 electrode with passivation layer

[0060] S1: Matrix porous titanium MPT (24*24cm 2 ) were immersed in a 0.5 M oxalic acid solution, heated to 80 °C in a water bath, and stirred continuously for ten minutes; then rinsed three times with deionized water and ethanol, and dried naturally;

[0061] S2: Prepare 2.5 g / L chloroiridic acid ethanol solution, and then use a brush to evenly apply 3.6 ml of chloroiridic acid ethanol solution on the surface of the MPT prepared in S1, ensuring that the coating amount of the iridium source is controlled to 0.0625 mgIr / cm 2 (based on pure iridium), and then kept at 450 °C in a muffle furnace for 30 minutes to obtain an MPT containing an IrO2 anti-passivation layer;

[0062] S3: mixing chloroiridic acid, nano-IrO2 and polymer binder Nafion in a mass ratio of 1:2:4, and performing ultrasonic treatment in an ice-water bath for 30 minutes to form a uniform dispersion;

[0063] S4: Then, the dispersion prepared in S3 is quickly sprayed on the MPT containing the IrO2 anti-passivation layer prepared in S2 using an ultrasonic sprayer at a speed of 10 μl / s, and then dried at 60°C to constant weight;

[0064] S5: Finally, the electrode prepared in S4 was transferred to a muffle furnace and subjected to high temperature heat treatment at 450°C for 30 minutes in an air atmosphere with a heating rate of 10°C / min.

[0065] Embodiment 2:

[0066] The same preparation method as in Example 1 was used, except that:

[0067] In step S2, the amount of chloroiridic acid ethanol solution used is 7.2 mL, and the iridium loading of the IrO2 anti-passivation layer formed by heat treatment is 0.1 mg / cm 2 , the rest is the same as in Example 1.

[0068] Embodiment 3:

[0069] The same preparation method as in Example 1 was used, except that:

[0070] In step S2, the amount of chloroiridic acid ethanol solution used is 14.4 ml, and the iridium loading of the IrO2 anti-passivation layer formed by heat treatment is 0.2 mg / cm 2 , the rest is the same as in Example 1.

[0071] Figure 1-3 Shown are optical images of the passivated MPT prepared in Examples 1-3, respectively. Figure 4 This is the oxygen evolution linear voltammetric curve of the porous IrO2 electrode prepared in Example 1-3 in 0.01M sodium sulfate solution.

[0072] Figures 1 to 3 Loadings of 0.05, 0.1 and 0.2 mg were shown respectively I r / cm 2 The MPT of the iridium-loaded passivation layer can be intuitively obtained from the color. As the IrO2 content increases, the electrode gradually transitions from dark purple to blue. The oxygen evolution performance of the electrode was evaluated using the previous oxygen evolution performance evaluation method. Figure 4 The linear voltammetric curve analysis shows that as the Ir loading of the anti-passivation layer increases, the curve moves to the left, indicating that the oxygen evolution potential decreases at the same current density. Based on the above analysis, it can be seen that the amount of IrO2 on the substrate has a great influence on the oxygen evolution performance of the electrode.

[0073] Comparative Example 1:

[0074] A commercial porous IrO2 electrode (momentum conservation, mH2-Ti-200-Ir) was used as a control group, and the CO2 reduction performance of the commercial anode was evaluated in a two-electrode system electrolyzer. The specific scheme is as follows:

[0075] S1: Cut 3*3cm 2 Commercially prepared porous IrO2 with Nafion as the polymer binder;

[0076] S2: Cut 2.5*2.5cm 2 Area of ​​self-made Ag carbon paper (250 μm thick) electrode (2 mg / cm 2 );

[0077] S3: The cathode uses a 200μm PTFE gasket, the anode uses a 180mm PTFE gasket; the diaphragm uses a PiperION A40 anion diaphragm, eight M6 nuts, and the nuts are tightened with a force of 8N / m;

[0078] S4: The anode is passed through a 60°C 1M KOH solution for cyclic activation for 5 hours, and then pure water is used to circulate the KOH at the anode and the temperature of the electrolytic cell is lowered to room temperature.

[0079] S5: The carbon dioxide flow rate is 30 ml / min, the anode liquid is pure water, and its flow rate is 30 ml / min. Test its 50 mA cm -2 Cell voltage at current density.

[0080] Embodiment 4:

[0081] The anode oxygen evolution electrode used is the electrode prepared in Example 2. The other experimental conditions are the same as those in Control Example 1.

[0082] Figure 5 The actual pictures of the anode electrodes before and after the test of Control Example 1 and Example 4 and the quality changes before and after the test; Figure 6 This is the curve of the tank pressure changing with time in Example 4-5.

[0083] Figure 5 The data shows that compared with commercial electrodes, the nano-IrO2 on the surface of the homemade IrO2 / MPT electrode has a stronger adhesion. After 100 hours of stability testing, the catalyst shedding rate on the surface of the electrode of Control Example 1 is as high as 50.4%, while the catalyst shedding rate on the electrode of Example 4 is only 4.6%. The homemade electrodes can basically be reused. Figure 6 It shows that the activity of the homemade IrO2 / MPT electrode is better than that of the commercial electrode. The cell voltage of the homemade IrO2 / MPT electrode is 2.95V, which is lower than 3.40V of the control example 1.

[0084] In summary, IrO2 generated by heat-treating iridium source can not only coat nano-IrO2 and be loaded on the MPT surface, but also show better activity and greatly improved stability compared with commercial porous IrO2 electrodes.

[0085] All of the above are primary implementations of this intellectual property and do not set limitations on other forms of implementation of this new product and / or new method. Those skilled in the art will use this important information and modify the above content to achieve similar implementations. However, all modifications or transformations based on the new product of this invention belong to the reserved rights.

[0086] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. An electrolytic cell stack with high oxygen evolution performance, characterized in that: The anode used is an IrO2 oxygen evolution electrode, and the specific preparation method includes: In the first step, the porous support is acid-etched to remove the surface oxide layer; The second step is to heat treat part of the iridium source to form a small amount of IrO2 anti-passivation layer on the surface of the porous support; The third step is to prepare a mixture of iridium source, nano-IrO2 and polymer binder; The fourth step is to spray the mixture prepared in the third step uniformly on the surface of the porous support body treated with anti-passivation in the second step; The fifth step is to decompose the polymer binder in the sprayed mixture through heat treatment, and make the IrO2 formed by the iridium source coat the nano-IrO2 and load it on the surface of the porous support body that is resistant to passivation treatment, so as to obtain a highly active and highly stable porous IrO2 electrode.

2. The electrolytic cell stack with high oxygen evolution performance according to claim 1, characterized in that: The iridium source comprises at least one of chloroiridic acid, potassium hexachloroiridate, ammonium chloroiridate, ammonium chloroiridate, iridium trichloride and iridium acetate.

3. The electrolytic cell stack with high oxygen evolution performance according to claim 1 or 2, characterized in that: The porous support body includes at least one of titanium felt, matrix porous titanium (MPT), foam titanium, foam iron, foam nickel iron, carbon paper and carbon cloth.

4. The electrolytic cell stack with high oxygen evolution performance according to claim 1 or 2, characterized in that: The polymer binder includes at least one of Nafion, polyvinyl alcohol, carboxymethyl cellulose, epoxy resin and polyacrylamide.

5. The electrolytic cell stack with high oxygen evolution performance according to claim 1 or 2, characterized in that: In the second step, the loading range of IrO2 anti-passivation layer is 0.05-0.2 mg / cm 2 .

6. The electrolytic cell stack with high oxygen evolution performance according to claim 1 or 2, characterized in that: In the third step, the mass ratio of the iridium source, nano-IrO2 and polymer adhesive is controlled to be 1:2:

4.

7. Application of the electrolytic stack according to any one of claims 1 to 6 in waste gas carbon dioxide treatment and water electrolysis to produce hydrogen.

8. An anode IrO2 oxygen evolution electrode prepared by the method described in claim 1.

9. The anode IrO2 oxygen evolution electrode according to claim 8, characterized in that: Iridium oxide loading is 0.1-0.3 mg / cm 2 .

10. Use of the anode IrO2 oxygen evolution electrode according to claim 8 or 9 in anode oxygen evolution reactions of carbon dioxide reduction, proton exchange membrane water electrolysis to produce hydrogen, and nitrogen reduction.

Citation Information

Cited By

  • Preparation method of particle-self-supporting coupling oxygen evolution electrode for electrooxidation induction material local phase change

    CN121204721A